INTEGRATING SOCIO-CULTURAL KNOWLEDGE INTO FOREIGN LANGUAGE TEACHING: ENHANCING LANGUAGE COMPETENCE AND INTERCULTURAL COMMUNICATION - Gulnoz Yormatova Qayumovna (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical and practical foundations of integrating socio-cultural knowledge into the foreign language teaching process. It explores contemporary pedagogical approaches to developing intercultural communicative competence based on the inseparable relationship between language and culture. Particular attention is paid to the pedagogical potential of Content and Language Integrated Learning (CLIL), Task-Based Language Teaching (TBLT), and Project-Based Learning (PBL) in foreign language education. The study demonstrates how these approaches contribute to the development of learners’ linguistic, sociolinguistic, pragmatic, and intercultural competencies. Furthermore, it highlights the educational value of authentic cultural materials, digital learning resources, and innovative pedagogical technologies in fostering communicative competence, critical thinking, and intercultural awareness. The findings indicate that the systematic integration of socio-cultural components into foreign language instruction not only strengthens learners' language proficiency but also promotes tolerance, global citizenship, and effective intercultural collaboration. Consequently, this approach is considered one of the key factors in improving the quality of foreign language education in Uzbekistan and preparing competitive professionals capable of meeting international educational standards.